2013
DOI: 10.1590/s0080-623420130000400025
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do website educacional em Primeiros Socorros

Abstract: RESUMOAvaliar a estrutura, a qualidade da informação e a navegabilidade do website em Primeiros Socorros. A avaliação foi realizada por profissionais de informática, da saúde e por estudantes, utilizando-se instrumentos específicos e validados. O método Kappa foi aplicado para avaliar a concordância das respostas e o coeficiente α de Cronbach, para avaliar a confiabilidade do instrumento. Nas respostas obtidas pelos profissionais, observou-se que não houve concordância das respostas dos profissionais de inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
0
14
0
7
Order By: Relevance
“…28 Interactive tools such as forums, chats, e-mails, and others are usually available in VLE platforms, since they are organized spaces for didactic-pedagogical purposes that, combined with the teachers' and tutors' work, have contributed to a more interactive format in remote education. [29][30] The online course of this study on Health Education in Diabetes Mellitus was developed with four modules, text and article reading and interpretation, resolution of case studies, chats, forums, wherein the participants were assisted by teachers and tutors responsible for the course's organization and for monitoring in the institutional VLE. In general, the Nursing students evaluated that the features were met; however, less than two percent indicated that these features were partially met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Interactive tools such as forums, chats, e-mails, and others are usually available in VLE platforms, since they are organized spaces for didactic-pedagogical purposes that, combined with the teachers' and tutors' work, have contributed to a more interactive format in remote education. [29][30] The online course of this study on Health Education in Diabetes Mellitus was developed with four modules, text and article reading and interpretation, resolution of case studies, chats, forums, wherein the participants were assisted by teachers and tutors responsible for the course's organization and for monitoring in the institutional VLE. In general, the Nursing students evaluated that the features were met; however, less than two percent indicated that these features were partially met.…”
Section: Discussionmentioning
confidence: 99%
“…VLEs and the online complementary trainings augment the impact of information transmission in large amounts of time and long-distance contact. 29 Activities applicability responded to the students' expectations; however, there was a warning on the part of the participants to the case studies applied which demanded little reasoning. In another study, 11 students classified the "time management" and "self-discipline" items as moderately adequate for online teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, this criterion is not explicit, but is used in the context of other criteria. This can be seen in the examples of two national studies 30,32 . Accuracy is the fourth criterion.…”
Section: Criteria Proposed In Literaturementioning
confidence: 91%
“…It was labeled as "Design" by authors of this systematic review. Among national authors, six studies 12,19,22,[31][32][33] have also been concerned with this realm.…”
Section: Criteria Proposed In Literaturementioning
confidence: 99%
See 1 more Smart Citation